Study on health risk factors as a basis to implement programs that promote a nutritional culture in students of the la Sabana University - Sandra Rodriguez; Mariagracia Martínez; Franco Segnini; Valentina Cajiao; Iván Aivasovsky; Luis Gustavo Celis; Jaime Ayala; Catalina Rozo; Amparo Russi; Vilma Giratá; Carmen Cecilia Almonacid (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Nowadays the importance of lifestyles in the prevention of type 2 diabetes and the metabolic syndrome has been largely accertained. Objective. The purpose of our work is to implement programs that promote a nutritional culture in adolescents and young adults of the La Sabana University. Methods. The methodology entailed, after the corresponding informed consent, taking measures of the triceps and supraescapular skinfolds, waist circumference, body mass index (BMI), lean mass, and fat mass. Fasting blood samples were also taken to quantify cholesterol, triglycerides, high density lipoprotein (HDL) and low density lipoprotein (LDL). Results. The results obtained show that of the 165 students, 10.3% were underweight, 13.93% were overweight and 0.6% were obese. With regards to gender, 4.8% of the men and 9% of the women were overweight, 3% of the men and 7.2% of the women were underweight, and 0.6% of the women were obese. The blood chemistry showed that 30% had hypercholesterolemia, 18% hypertriglyceridemia, 17% reported low HDL levels and 67% reported high LDL levels. Of all the cases studied, 40% are at risk of a metabolic syndrome. 60% claimed not to practice any physical activity - especially women who reported 44.70%. Conclusions. These findings have allowed us at the institution to implement a culture of healthy habits. The have also allowed us to identify students with risk factors for type 2 diabetes and metabolic syndrome. This is why the cardiometabolic monitoring and control based on healthy eating and physical activity are important.